VALIDITAS PENGEMBANGAN LKPD BAHASA INDONESIA BERBASIS MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD - Dea Andini; Herpratiwi; Munaris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the findings of the needs analysis conducted at SDN 2 Sawah Brebes. Based on the results of the needs analysis, it was found that the critical thinking skills of fifth grade students were low. Mind Mapping-based Indonesian LKPD to Improve Critical Thinking Skills was developed as a solution to the low critical thinking skills. In order for the developed LKPD to be of high quality, a validity test was carried out. Based on the validity test conducted, Mind Mapping-based Indonesian LKPD to Improve Critical Thinking Ability meets the valid criteria in material and language aspects and is very valid in media aspects.